Recent updates in the management of iron deficiency anemia in Indian patients: literature review and expert opinion - Anand, Chandrika; Singh, Rakhi; Tiwari, Varsha; Gala, Monil; Muchhala, Snehal; Kotak, Bhavesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Iron deficiency anemia (IDA) is a global issue, particularly affecting pregnant women and children in India. It can lead to severe outcomes such as preterm birth, low birth weight, and increased maternal and perinatal risks. An expert panel of Indian obstetrics and gynecology specialists reviewed the literature and proposed recommendations on IDA's prevalence, diagnosis, management, and challenges such as healthcare access, patient education, and awareness. Management strategies for IDA include dietary adjustments and lifestyle changes, alongside pharmacological treatments, including oral and parenteral iron therapy. Oral iron, though accessible, can cause gastrointestinal side effects, and prevailing misconceptions about its impact on fetal growth affect adherence. Intravenous (IV) iron administration should be considered for patients who experience intolerance, poor adherence, or lack of efficacy with oral iron. Ferric carboxymaltose, a newer IV formulation, is gaining popularity due to its rapid iron replenishment, efficacy and safety, single infusion convenience, and cost-effectiveness in treating pregnant women. Public health initiatives in India like National Nutritional Anemia Control Program and Anemia Mukt Bharat aim to reduce IDA through supplementation programs and education. However, challenges like low adherence to iron supplementation, parasitic infections, and micronutrient deficiencies remain. Overcoming these requires a comprehensive approach, including patient education and effective public health strategies. According to the expert recommendations, managing IDA during pregnancy is vital for maternal and fetal health. A combination of dietary modifications, pharmacological treatments, and public health interventions is crucial to combat this prevalent condition in India and improve maternal and fetal health outcomes.